2017
DOI: 10.1111/jcpt.12567
|View full text |Cite
|
Sign up to set email alerts
|

Type of oral solid medication packaging and medication preparation time in nursing homes: A direct observation study

Abstract: To our knowledge, we were the first to examine the effect of type of oral solid medication packaging on medication preparation time in nursing homes. Type of packaging matters. The time saved using strip packaging (vs bingo card packaging) has implications for quality of care and the movement towards person-centred care in the nursing home sector. Nurses (or other staff tasked with medication preparation) in nursing homes using strip packaging potentially have more time to devote to nurturing a relationship wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Additionally, adjustments in the distribution system allows the nursing staff to spend more time in providing direct patient care. Studies have shown that nurses spend a substantial amount of time preparing and administering medications; the greater the number of drugs, the greater the time spent [17][18][19] . In a study conducted in American LTCFs, individualizing doses in a manner similar to that adopted in the present study considerably reduced the time spent preparing the medications 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, adjustments in the distribution system allows the nursing staff to spend more time in providing direct patient care. Studies have shown that nurses spend a substantial amount of time preparing and administering medications; the greater the number of drugs, the greater the time spent [17][18][19] . In a study conducted in American LTCFs, individualizing doses in a manner similar to that adopted in the present study considerably reduced the time spent preparing the medications 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that nurses spend a substantial amount of time preparing and administering medications; the greater the number of drugs, the greater the time spent [17][18][19] . In a study conducted in American LTCFs, individualizing doses in a manner similar to that adopted in the present study considerably reduced the time spent preparing the medications 19 . Although the impact on the time spent preparing the medications was not evaluated in our study, the staff indicated greater availability for patient care provision.…”
Section: Discussionmentioning
confidence: 99%
“…Three metropolitan private, not‐for‐profit RACFs operated by the same South Australian aged care provider organizations participated. Medications were supplied to these RACFs in pre‐packed medication strip packaging 28 . Paper‐based medication administration charts were used for documentation.…”
Section: Methodsmentioning
confidence: 99%
“…The most common systems are reusable, multi-compartment, cassette-format MODs made from rigid, thermosetting polymers and disposable MODs made from thermoplastics, thus easier to seal. The latter come in the formats of blister pouches (also known as sachets or strip packaging), blister cards with a cardboard frame (also known as punch cards or "bingo" cards) and foil-sealed cups [16][17][18]. Some of the disposable MODs are marketed as capable of accommodating liquids [13].…”
Section: Introductionmentioning
confidence: 99%